2011
DOI: 10.1155/2011/870385
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Comorbid Obesity and Major Depressive Disorder: A Prospective Pilot Study for their Combined Treatment

Abstract: Background. Obese individuals who suffer from major depressive disorder are routinely screened out of weight loss trials. Treatments targeting obesity and depression concurrently have not been tested. Purpose. To test the short-term efficacy of a treatment that combined behavioral weight management and cognitive behavioral therapy (CBT) for obese adults with depression. Methods. Twelve obese females diagnosed with major depressive disorder received weekly group behavioral weight management, combined with CBT f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
(22 reference statements)
0
16
0
1
Order By: Relevance
“…Obesity and depression have bi-directional relationship and they often occur together [39], however, there have been no studies on combination therapy among individuals with obesity and depression. In a pilot study it was documented that individuals who were provided CBT for depression along with evidence-based behavioral treatment for obesity achieved a clinically significant reduction in depressive symptoms in 16 weeks [40]. Therefore, it is plausible that those with obesity and depression may receive treatments that combine psychotherapy for depression to achieve better clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and depression have bi-directional relationship and they often occur together [39], however, there have been no studies on combination therapy among individuals with obesity and depression. In a pilot study it was documented that individuals who were provided CBT for depression along with evidence-based behavioral treatment for obesity achieved a clinically significant reduction in depressive symptoms in 16 weeks [40]. Therefore, it is plausible that those with obesity and depression may receive treatments that combine psychotherapy for depression to achieve better clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These results provided initial evidence that obese individuals with MDD could lose weight. More encouraging results were yielded by Faulconbridge and colleagues [107•] who conducted a pilot study with 12 obese, depressed individuals who received a combination of lifestyle modification for their obesity and cognitive-behavioral therapy for their depression for 16 weeks. The mean weight loss among those who completed the study was 11.4% of initial weight, comparable to the magnitude of weight loss observed in non-depressed participants undergoing lifestyle modification interventions [100].…”
Section: Outcomes For Depressed Individuals In Weight Loss Trialsmentioning
confidence: 99%
“…As such, it may be prudent to moderate the weight loss expectations of depressed individuals undertaking weight reduction. In addition, a small minority of patients do experience adverse psychological events during weight loss [89,107], and thus careful monitoring of mood in all individuals who undertake weight loss is advisable.…”
Section: Outcomes For Depressed Individuals In Weight Loss Trialsmentioning
confidence: 99%
“…[7] An uncontrolled trial evaluated simultaneous lifestyle intervention and CBT for depression reported much larger weight loss (i.e., mean weight loss of −10.4 kg) than typically observed in either depressed or nondepressed samples but only included 9 participants. [8] Another small uncontrolled trial tested the simultaneous delivery of a lifestyle intervention and brief behavior therapy for depression in 14 individuals [9] and found significant changes in weight and depression, however weight loss was also modest (i.e., mean = −2.5 kg) relative to nondepressed samples. [7] Given that the bulk of the evidence shows that people with depression lose less weight than their non-depressed counterparts, specialized interventions appear to be needed.…”
Section: Introductionmentioning
confidence: 99%